Factors beyond Lack of Knowledge That Predict "I Don't Know" Responses to Surveys That Assess HPV Knowledge. Issue 10 (2nd November 2018) - Ellis, Erin M.; Ferrer, Rebecca A.; Klein, William M. P.
Abstract : Accurately assessing the public's knowledge about the human papilloma virus (HPV) and the HPV vaccine remains critical for informing health education interventions aimed at increasing vaccine uptake. Responding "don't know" (DK) to survey questions that assess knowledge is common and DK responders are often systematically different from other responders, resulting in potential for bias. This study aimed to advance our understanding of DK responding to HPV knowledge items. Data from the nationally representative Health Information National Trends Survey Wave 5 Cycle 1 ( N = 2, 034) were used. Information seeking about cancer, information avoidance, health-related self-efficacy, and several cancer beliefs were examined as predictors of DK responding to six items that assessed HPV knowledge. DKs represented nearly half of responses. Adjusting for demographic factors, lower health-related self-efficacy, and greater information avoidance, cancer-mortality salience, and perceived ambiguity were associated with more DK responding, p s < .05. Even participants with incorrect responses had greater health-related self-efficacy, and less information avoidance, perceived ambiguity, and cancer-mortality salience than those who responded with DK. DK responding to HPV knowledge items is common and reflects factors beyond insufficient knowledge or motivation. Addressing causes of DK responding may reduce bias and improve interventions informed by surveys.